Long-term landscape evolution and post-rift reactivation in the southeastern Brazilian passive continental margin: Taubat, basin - Franco-Magalhaes, A. O. B.; Cuglieri, M. A. A. [UNESP]; Hackspacher, P. C. [UNESP]; Saad, A. R. (Springer, 2014)
Zircon (ZFT) and apatite (AFT) fission-track low-temperature thermochronology was applied at the Brazilian passive continental margin in order to understand and reconstruct the post-rift evolution since the breakup of southwestern Gondwana. The thermochronological data obtained from samples of both the Precambrian basement and the Paleogene to Neogene sedimentary rocks from the continental rift of southeastern Brazil provided ZFT ages between 148 (15) and 64 (6) Ma, and AFT ages of 81 (8)-29 (3) Ma. These data clearly indicate syn- and post-rift reactivations during the Early Cretaceous, with great emphasis on Paleogene to Neogene times. Integrating the results of older thermochronological studies, the reactivation of the southeastern Brazilian margin can be described in three main phases related to the rift to post-rift evolution of SE Brazil. In general, ZFT and AFT data yield spread values that become younger as samples are closer to the reactivated Neoproterozoic shear zones and might reflect source area exhumation. The analysis of ZFT and AFT data allowed interpretations regarding the main phases that occurred in the study area related to the thermotectonic and tectono-stratigraphic evolution in southeastern Brazil.
Keywords: Low-temperature thermochronology; Continental rift of southeastern Brazil; Late cretaceous-Paleogene reactivation; Post-rift exhumation